As estratégias de marketing internacional de empresas de floricultura do Ceará: estudos de caso - Esteves, Bruno José Pereira (2006)
A relevant economical and marketing phenomenon in the state of Ceará consists of the growing internationalization of its floriculture business, with crescents and high volumes of sales for external markets, which are frequently referred in means of social communication. The present work has the objective of analyzing this phenomenon, with emphasis in the factors that contributed to the present growth of the business in the context of the international market, and consequently to know which are the strategies and marketing tactics used by the business companies for their external customers. The theoretical references leans over on the theme of the internationalization as an economical and corporate phenomenon, as well as it approaches strategy theories and international marketing, the essential focus of the work, also existing references to theory related with agrobusiness and floriculture. The chosen methodology for the research assumes the forms of documental, historical and case studies, appropriate methods for the type of results and depth intended for the research, which is uncoiled in different phases, but interlinked. The data obtained in the phases of the research reveals that the business owes its current success to a varied group of factors, contained through the use of the "diamond model" suggested by Michael Porter for the analysis of competitive advantages of a cluster heading for its internationalization. These results allow a better framing with the business in the following phase of research, which seeks to reach the objective of knowing which are the strategies of international marketing of companies of floriculture of the state of Ceará. The results of this phase of the research reveal that in spite of the good results reached by the section, an egg white apprehension the advantages of the internationalization and good knowledge of the product, the form as the studied companies work with the foreign customers and the marketing tactics used by them demonstrate that they do not apply deliberate strategies and properly delineated to these markets, suggesting some risk factors and the need of some future orientations, with the sense of maintaining the current success of the section